No assemblage required: On pursuing original consumer culture theory. (December 2019) - Belk, Russell; Sobh, Rana
Our title plays with the promise on certain consumer goods packages of "no assembly required, " but in fact we call upon the reader to assemble new theories rather than rely on existing ones like assemblage theory. We argue that consumer culture theory (CCT), also known as interpretive consumer research, has thus far not fulfilled its potential as a theory-generating discipline. Our reluctance to attempt creative theorizing is institutionalized by calls for theory-enabled research rather than truly emergent theory. This retreat has recently been strengthened by the rise of Big Data and correlational approaches that eschew theory altogether. In order to change this situation, we recommend a three-stage approach: (1) original phenomena-driven inquiry, (2) combining grounded theory and abductive reasoning, and (3) generating and comparatively analyzing alternative theoretical explanations. We briefly conceptualize the first two stages and illustrate the third using an example of consumer brand masking and bluffing in Africa. We demonstrate the use of two criteria for comparative theoretical analysis: (a) fit with the data and (b) potential usefulness in other contexts. We also argue that sometimes multiple theories are needed. CCT researchers are uniquely positioned to pursue original theory, and in this article, we offer some ideas as to how this can be done.